Ada Apa Dengan SKMHT? - Dyah Rahmanti, Novy (Recital Review, 2020)
Notary authority in making the power of attorney imposing Collateral Right (SKMHT) made under the Notarial deed based on Article 96 paragraph (1) of the Regulation of the Head of Land Board No.8/2012 related to Article 38 of Law on Notary Position No.30/2004 (UUJN) is a problem which is, in practice, faced by Notary/Land Certificate Issuing Officer in performing his/her duty as a Public Official making and issuing authentic deed. The SKMHT made under the notarial deed should be regulated in Article 38 of of Law No. No.30/2004 (UUJN) not in Article 96 paragraph (1) of the Regulation of the Head of Land Board No.8/2012 which regulates te authentic deed for the Land Certificate Issuing Officer (PPAT). The deed of SKMHT is not a guarantee institution like the existing guarantee institution but only a Power of Attorney (Authentic) from the debtor /guarantor to the creditor/collateral receiver in a series of early process of the implementation of Collateral Right binding on the object of credit collateral such as a plot of land, therefore, the position of SKMHT deed has not yet had an executorial power on the land/the collateral object. Research methodology in this research is normative juridical research method with statute approach and case approach. The law substances include primary, secondary and tertiary law substance.The result of this study showed that the SKMHT made under the Notarial deed which should be regulated and object to Article 38 of Law No. No.30/2004 (UUJN) was not realized because the Office of National Land Board (BPN) will not process the SKMHT with this provision, except SKMHT uses the format in accordance with the condition in Article 96 paragraph (1) of the Regulation of the Head of Land Board. T using blank SKMHT, then the Notary has acted outside his authority, so the SKMHT does not have proof power as an authentic deed in protect the rights of creditors.